Influência do ácido hipocloroso obtido a partir de um dispositivo eletrolítico na resistência flexural da dentina radicular – estudo in vitro - Pizzi, Camila Yasmin Monteiro (2023)
The aim of the present study was to evaluate, in vitro, the influence of hypochlorous acid obtained from an electrolytic device on the flexural strength of root dentin. For the flexural strength test, crowns of 30 bovine teeth were removed, and the roots were sectioned to obtain root dentin fragments. The samples were made in a standardized size, in a rectangular shape and, in all, 60 dentin sticks were produced. The samples obtained were randomly distributed into 3 groups and subjected to irrigation protocols (n=20), with group 1 - distilled water (control group); Group 2 - Sodium hypochlorite (2.5% NaOCl); Group 3 - Hypochlorous acid (HClO 250ppm). Each sample was submerged in 2 ml of the appropriate substance in an Eppendorf tube. To avoid the continuous action of irrigants on dental surfaces, all samples were washed with 5ml of distilled water and dried with gauze after submerging the substances. The flexural strength test was performed using a Universal Testing Machine using the three-point method, with a load in MPa being applied to the central portion of the toothpick at a speed of 0.5 mm/minute until fracture, the value being expressed in Megapascal (Mpascal ). Tukey's one-way ANOVA and post-hoc statistical analysis was performed (α=5%). The results of the study showed that the highest values of flexural strength (Mpa) were found in groups 1 (control) and 3 (HClO), being statistically different from group 2 (NaOCl) (p<0.05). It can be concluded that the hypochlorous acid obtained from an electrolytic device did not interfere with the flexural strength of root dentin.